2007
DOI: 10.1002/cmdc.200600244
|View full text |Cite
|
Sign up to set email alerts
|

Model Systems for Fluorescence and Singlet Oxygen Quenching by Metalloporphyrins

Abstract: Next-generation photodynamic therapy agents will minimize extraneous phototoxicity by being active only at the target site. To this end, we have developed a model system to systematically investigate the excited-state quenching ability of a number of metalloporphyrins. Central metal ions that prefer four-coordinate, square planar orientations (Ag(II), Cu(II), Ni(II), Pd(II), and Zn(II)) were used. Porphyrin dimers based on 5-(4-aminophenyl)-10,15,20-triphenylporphyrin and comprising both a free base porphyrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…It was proposed that the Fe II metal centers could be responsible for lowering of the quantum yield of 1 O 2 generation by reducing the spin–orbit coupling necessary for efficient intersystem crossing . Furthermore, several transition‐metal complexes (Ni II , Cu II , and Ag II ) are reported in the literature as moderate‐to‐excellent excited‐state quenchers . In particular, the paramagnetic metal center Cu II , with its d 9 valence‐electron configuration, has been shown to increase the quenching efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that the Fe II metal centers could be responsible for lowering of the quantum yield of 1 O 2 generation by reducing the spin–orbit coupling necessary for efficient intersystem crossing . Furthermore, several transition‐metal complexes (Ni II , Cu II , and Ag II ) are reported in the literature as moderate‐to‐excellent excited‐state quenchers . In particular, the paramagnetic metal center Cu II , with its d 9 valence‐electron configuration, has been shown to increase the quenching efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…[42] Furthermore, several transition-metal complexes (Ni II ,C u II ,a nd Ag II )a re reported in the literature as moderate-to-excellent excited-state quenchers. [43] In particular, the paramagnetic metal center Cu II ,w ith its d 9 valence-electron configuration, has been shown to increaset he quenching efficiency.T he Zn-porphyrin fluorescenceq uenching upon Cu II binding to the periphery of the porphyrin ring during the synthesis of porphyrin-metal receptord yads has been reported. [44] Steady-statef luorescencea nd lifetime measurements demonstrated that the photoexcited singlet state of the Zn-porphyrin ( 1 (ZnP)*) is quenched by ap endant [Cu II (edta)] 2À (edta = ethylenediaminetetraacetate) complex tethered to the ZnTPP chromophoreb yi ntramolecular photoinduced electron transfer.…”
Section: Guest-dependent Tuningof 1 O 2 Productionmentioning
confidence: 99%
“…To date, activatable PSs have been constructed as lowmolecular-weight systems such as PS-PS conjugates (McCarthy & Weissleder, 2007), PS-quencher conjugates (Lovell et al, 2009) or PS-singlet oxygen scavenger conjugates (Chen et al, 2007). Low-molecular-weight systems have limitations, such as the rapid elimination of conjugates from the body and the development of multiple drug resistance; these issues can result in short plasma half-life and low bioavailability (Master, Livingston, & Sen Gupta, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…endothelium), as seen in Figure 1. The overall aim of PDTs is to stop the biological activities of macrophage cells in atheromatous plaques by necrosis, as described previously in the work of McCarthy et al [14][15][16][17] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%